PERBANDINGAN NILAI INDEKS PRODUKTIVITAS INDUK KAMBING SABURAI DAN KAMBING PERANAKAN ETAWA PADA BOBOT SAPIH DI UNIT PELAKSANAAN TEKNIS DAERAH NEGERI SAKTI, PROVINSI LAMPUNG - Gilang Wahyu Kartiko; Muhammad Dima Iqbal Hamdani; Dian Kurniawati; Kusuma Adhianto (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2021)
This study aimed to compare the value of does productivity index of Saburai goats and Etawa Grade (EG) goats in UPTD Negeri Sakti, Lampung Province. This research used 25 female Saburai goats and 25 female EG goats with their first and second parity kids. This study used a survey method with collecting data by census method. The variables observed were litter size, kidding interval, birth type, corrected weaning weight. The results showed that the average litter size of Saburai goats and EG goats were 1.34 ± 0.37 and 1.82 ± 0.35, respectively. Kidding interval of Saburai and EG goats was 7.01 ± 0,17 months and 8.69 ± 0.38 months, respectively, the mean of corrected weaning weight of Saburai goats was 18.64 ± 2.01 kg while of EG goats was 12.69 ± 1.15 kg. The mean does productivity index of Saburai goats and EG goats were 42.71 ± 12.32 and 32.35 ± 8.41, respectively. The results also indicated that does productivity index of Saburai goats was different from that of EG goats. Keywords: Does productivity index, Ettawa Grade goat, kidding interval, Saburai goat, weaning weight